Constructing sub-Saharan African mobilities through the flow of second-hand objects: Scripting bicycles for Namibian users. (February 2020) - Baker, Lucy
Abstract: This article examines how civil society operates to configure mobilities for development contexts and subjects. In order to understand the politics and processes of constructing mobilities and the potential for decolonising mobility design, the paper traces the flow of second-hand bicycles from the global North to Namibia using a framework of Script Analysis. The issues of power in constructing social and technical meanings attributed to the bicycles are examined as they are re-valued for humanitarian use. The paper investigates how Namibian users subscribe to, reject and adapt the bicycles' meanings and physical properties in order suit their diverse needs, which are often disparate from techno-rational understandings of transport solutions for economic development. The analysis finds that the bicycle is prescribed singularly as an object that intends to technologically modernise utilitarian subjects in a universal development imaginary. Simultaneously, alternative framings of mobility, for example the way in which bicycles are appropriated to perform modern and global identities, are discouraged in hegemonic mechanisms of development.